2022
DOI: 10.1371/journal.pntd.0010208
|View full text |Cite
|
Sign up to set email alerts
|

A symbiotic gut bacterium enhances Aedes albopictus resistance to insecticide

Abstract: Background The increasing insecticide resistance of Aedes albopictus puts many countries in Asia and Africa, including China, at great risk of a mosquito-borne virus epidemic. To date, a growing number of researches have focused on the relationship between intestinal symbiotic bacteria and their hosts’ resistance to insecticides. This provides a novel aspect to the study of resistant mechanisms. Methods/Findings This study reveals significant composition and dynamic changes in the intestinal symbiotic bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…pipiens in mosquito control operation areas [ 48 , 49 ]. Recent studies have indicated that symbiotic bacteria enhance mosquito resistance by directly breaking down the insecticide and increasing their metabolic enzyme activity [ 6 , 9 ]. Nonetheless, the impact of symbiotic bacteria on target site susceptibility has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pipiens in mosquito control operation areas [ 48 , 49 ]. Recent studies have indicated that symbiotic bacteria enhance mosquito resistance by directly breaking down the insecticide and increasing their metabolic enzyme activity [ 6 , 9 ]. Nonetheless, the impact of symbiotic bacteria on target site susceptibility has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There are notable disparities in the composition of intestinal microbial communities between insecticide-sensitive and -resistant mosquitoes. Asiaia and Serratia bacteria have been observed to contribute to the development of mosquito sensitivity to deltamethrin; for example, Serratia oryzae can significantly enhance the resistance of Aedes albopictus to deltamethrin by upregulating the expression of metabolic detoxification genes [ 6 , 7 ]. Our previous study identified Aeromonas hydrophila as the predominant bacterial species in the intestinal tract of a deltamethrin-resistant strain of Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between generalists and specialists are also observed at the molecular level. For example neofunctionalisation of gene copies and horizontal gene transfer often enhances genomic flexibility in generalists to facilitate diverse host usages (Heidel-Fischer et al, 2019;Kirsch et al, 2014;Prasad et al, 2021;Wybouw et al, 2015). In addition, the genomes of polyphagous species often show dramatic expansion of chemosensory and detoxifying gene repertoire resulting in more remarkable plasticity during herbivory, which often accounts for the observed difference in the diet breadth between generalist and specialist insects (Grbić et al, 2011;Li et al, 2013;Xu et al, 2016).…”
Section: Box 3 Host Plant Utilisation: Generalist Versus Specialist S...mentioning
confidence: 99%
“…Herbivorous arthropods harbour gut microbiota that has been suggested to aid in plant allelochemical detoxification (Ceja‐Navarro et al, 2015; Després et al, 2007; Francoeur et al, 2020) even if its importance may vary between insect orders (Hammer et al, 2017). Endosymbionts have recently been shown to aid their arthropod host in detoxifying pesticides, but this area is still largely unexplored (Almeida et al 2017; Itoh et al, 2018; Le Goff & Giraudo, 2019; Wang et al, 2022). Gut microbiota may thus provide a phenocopy of cross‐resistance and the possibility for both horizontal and lateral transfer of microbe‐mediated resistance between individual arthropods (Acuna et al, 2012; Cheng et al, 2018; Rassati et al, 2019; Taerum et al, 2013).…”
Section: Cross‐resistance: Taking Ecology Into Accountmentioning
confidence: 99%
“…Due to the indiscriminate use of insecticides over the years, herbivorous insects, including CLB, have developed insecticide resistance (Tanasković et al, 2012 ). Several beetles adaptations have been identified to explain the reduced efficiency of insecticides, including (a) mutation of insecticide action sites (Obrępalska‐Stęplowska et al, 2016 ; Wrzesińska et al, 2014 ), (b) thickening of insect epidermis reducing insecticide penetration (Hemingway & Karunaratne, 1998 ; Rocha et al, 2021 ; South & Hastings, 2018 ; Wang et al, 2022 ), (c) increase in insecticide metabolism through up‐regulation of genes encoding enzymes such as cytochrome P450, monooxygenase, glutathione S‐transferase, carboxylesterase, acetylcholinesterase, hydrolase and many more associated with insecticide degradation (Chang et al, 2017 ; Cisse et al, 2015 ; Jaffar et al, 2022 ; Vontas et al, 2020 ; Wang et al, 2022 ; Wieczorek et al, 2014 ). The implication of symbiotic microbes as potential contributors to insecticide resistance is of great interest.…”
Section: Introductionmentioning
confidence: 99%